Thymosin β4 coated nanofiber scaffolds for the repair of damaged cardiovascular tissue - Kumar, Arun (Henry Stewart Talks, 2015)
Synthesis of the nanofiber scaffold, Preparation of thymosin beta-4 coating, Role of small molecules in cardiogenesis, Characterizations of coated nanofiber scaffold, Application of scaffold technology to heart repair